Solitary waves in a plasma with oppositely charged dust (heavier, pair ions) and kappa modeled lighter ions and electrons. (4th February 2015) - Sebastian, Sijo; Sreekala, G; Michael, Manesh; Abraham, Noble P; Renuka, G; Venugopal, Chandu
Abstract: We investigate the existence of compressive and rarefactive solitary waves in a five-component plasma. Positively and negatively multiply charged heavier ions (dust), kappa function described photo-electrons, hot electrons and ions form the five components. The pseudo-potential approach is used to determine the existence of a soliton. We find that the Sagdeev potential as well as the amplitude of the solitary wave for both compressive and rarefactive solitons increases with increasing spectral indices of the kappa distributions describing the cometary species. The magnitude of the amplitude of the solitary wave increases with increasing positively charged ion densities and charge numbers, but decreases with increasing charge numbers of the negative ions for both type of solitons.